Frequency, magnitude and character of hyperthermal events at the onset of the Early Eocene Climatic Optimum - V. Lauretano; K. Littler; M. Polling; J. C. Zachos; L. J. Lourens (Climate of the Past, 2015)
Recent studies have shown that the Early Eocene Climatic Optimum (EECO) was preceded by a series of short-lived global warming events, known as hyperthermals. Here we present high-resolution benthic stable carbon and oxygen isotope records from ODP Sites 1262 and 1263 (Walvis Ridge, SE Atlantic) between ~ 54 and ~ 52 million years ago, tightly constraining the character, timing, and magnitude of six prominent hyperthermal events. These events, which include Eocene Thermal Maximum (ETM) 2 and 3, are studied in relation to orbital forcing and long-term trends. Our findings reveal an almost linear relationship between δ 13 C and δ 18 O for all these hyperthermals, indicating that the eccentricity-paced covariance between deep-sea temperature changes and extreme perturbations in the exogenic carbon pool persisted during these events towards the onset of the EECO, in accordance with previous observations for the Paleocene Eocene Thermal Maximum (PETM) and ETM2. The covariance of δ 13 C and δ 18 O during H2 and I2, which are the second pulses of the "paired" hyperthermal events ETM2-H2 and I1-I2, deviates with respect to the other events. We hypothesize that this could relate to a relatively higher contribution of an isotopically heavier source of carbon, such as peat or permafrost, and/or to climate feedbacks/local changes in circulation. Finally, the δ 18 O records of the two sites show a systematic offset with on average 0.2 ‰ heavier values for the shallower Site 1263, which we link to a slightly heavier isotopic composition of the intermediate water mass reaching the northeastern flank of the Walvis Ridge compared to that of the deeper northwestern water mass at Site 1262.